Students’ perceptions on social media teaching tools in higher education settings - Figueras Maz, Mónica (2021)
Young people use social networks extensively in their daily lives, and using social media is, without doubt, the media practice they do the most. Therefore, there are increasing efforts to include students’ use of social media outside the classroom into university learning practices. However, there is still very little innovative application of mobile technology and its social networks in Spanish universities. In this article we explore Spanish university students’ perceptions of the use of social networks for educational purposes in the classroom. We found students to have an ambivalent perception as they are both critical and approving of using mobile devices in university teaching. We present data from the research project “Media competencies of citizens in emerging digital media in university environments” funded by the Ministry of Economy and Competitiveness of Spain. The study is based on 897 questionnaires given to Spanish university students studying various degrees, as well as four focus groups held in Seville, Madrid, Huelva and Barcelona during the 2017-2018 academic year. The data show that there is little use of social networks for educational and creative purposes in Spanish universities, and formal practices (organized by the teacher) are very different from informal practices (organized spontaneously by students). The latter is the most common among university students and WhatsApp is the most used internal tool, followed far behind by Facebook and Instagram. Students appreciate the direct and immediate communication of these networks, but are concerned about their distracting influen